Treg cells expressing the coinhibitory molecule TIGIT selectively inhibit proinflammatory Th1 and Th17 cell responses - Joller, Nicole; Lozano, Ester; Burkett, Patrick R; Patel, Bonny; Xiao, Sheng; Zhu, Chen; Xia, Junrong; Tan, Tze G; Sefik, Esen; Yajnik, Vijay; Sharpe, Arlene H; Quintana, Francisco J; et al. (Immunity (Cambridge, Mass.), 2014)
Foxp3(+) T regulatory (Treg) cells regulate immune responses and maintain self-tolerance. Recent work shows that Treg cells are comprised of many subpopulations with specialized regulatory functions. Here we identified Foxp3(+) T cells expressing the coinhibitory molecule TIGIT as a distinct Treg cell subset that specifically suppresses proinflammatory T helper 1 (Th1) and Th17 cell, but not Th2 cell responses. Transcriptional profiling characterized TIGIT(+) Treg cells as an activated Treg cell subset with high expression of Treg signature genes. Ligation of TIGIT on Treg cells induced expression of the effector molecule fibrinogen-like protein 2 (Fgl2), which promoted Treg-cell-mediated suppression of T effector cell proliferation. In addition, Fgl2 was necessary to prevent suppression of Th2 cytokine production in a model of allergic airway inflammation. TIGIT expression therefore identifies a Treg cell subset that demonstrates selectivity for suppression of Th1 and Th17 cell but not Th2 cell responses.